Development of an index for wheat stripe rust infection - De Wet, Linda (University of the Free State, 2001)
The main objective of this project was to develop an early warning index for infection of stripe rust (Puccinia striiformis f. sp. tritici) in susceptible cultivars of wheat (Triticum aestivum) for the main wheat growing areas of the R.S.A. Various authors are in agreement that temperature and moisture are the major climatic factors necessary for infection by stripe rust. Temperature limits from the literature vary between -4 and 30°C and no cut-off values were available. It was therefore decided to run an experiment to observe infection of stripe rust under conditions of high relative humidity and a range of temperatures, namely 5°C, 10°C, 15°C and 20°C. Results from the experiment indicated that little or no infection occurred for the 20°C temperature level and for exposure time periods of one hour or less. Exceptions occurred when sudden drops in temperature with removal of plants from growth chambers to the glasshouse took place. For both incidence and severity, it was found that temperatures greater than 22°C inhibited infection. The Pan 3349 cultivar was found to exhibit higher incidence than Karee. The statistical analysis shows significance for severity for Experiment 1 and 2, but not for incidence. Temperatures for Experiment 2 were slightly lower than those in Experiment 1 and could be explained by the presence of the fans in Experiment 2, to allow evaporation of dew from the sensors, allowing the sensors to register correct readings. The resulting higher moisture conditions in the still air In Experiment 1 could have contributed to the higher severity observed in Experiment 1. Conditions in the laboratory are not the same as in the field and possibilities for infections at higher temperatures in the field have been reported by Park (1990). He warned against extrapolation of results from the laboratory to the field, but it was nevertheless decided to use the results from the experiment as a basis for the development of an index for stripe rust infection of susceptible wheat cultivars in South Africa. Values of 14 day total degree days (TDDI4) were calculated from total degree hours (TDH) acquired from the experiment. TDDl4 for the experiment was calculated by summing degree days (DD) from inoculation until 14 days and relating them to average incidence observed on day 14. Two linear regression lines were obtained, one for 5°C 15°C temperature level and the other for the 15 °c - 20°C temperature levels. A cut-off TDDl4 value of 227 where the two lines crossed indicated 67 % cut-off value for incidence. TDDl4 was developed from this information and reads as follows: IfTDDI4> 227, then risk of incidence is low at < 67 %. IfTDDl4 < 227, then risk of incidence is high at > 67 %. TDDl4 was validated by testing on 1996 - 1998 and 1999 - 2000 data. Correct prediction values for highest and average incidence observation were 50 % and 29 % for 1996 - 1998 data (Table 4.7) and 40 % and 33 % for 1999 - 2000 data (Table 4.8). TDDl4 however, was thought to be impractical, so TDD7 was developed by using TDD7 for 7 days from a wet period. TDD7 = 128 was found to be 1.77 times less than the value for TDDl4 = 227 and so this value of 128 was used as the cut-off value. TDD7 thus reads as follows: If TDD7 > 128, then risk of incidence is low at < 67 %. If TDD7 < 128, then risk of incidence is high at > 67 %. TDD7 was validated using the 1999 - 2000 data, with total correct predictions of 53 % and 40 % (Table 4.10). It was therefore decided that TDD7 could be used by the producer as an early warning index, although the index would have to be tested in the field so that necessary improvements could be made. It is recommended that research on stripe rust-environment interaction be continued, also to include other diseases and the recommendations made in Chapter 2. Another possible recommendation would be to plan a refined laboratory experiment with a mechanistic approach to use a constant temperature data determined model in real life situations. Temperature and RH would vary and the results should be useful to producer, as well as the researcher. A model suitable for various other diseases as well, could be of great benefit when the cost of pesticides and fungicides are taken into account. The successful application of such a model would be of great benefit to all. After all, food is our fuel and sustainable production of high quality foodstuffs is essential to our survival.

Die hoofdoel van hierdie projek is om 'n waarskuwingsindeks te ontwikkel vir vatbare kultivars van koring (Triticum aestivum) vir infeksie deur Puccinia striiformis f. sp. tritici (streeproes of geelroes) in R.S.A. Volgens die literatuur is outeurs grotendeels eens dat temperatuur en vogtigheid die hoof klimaatsfaktore vir infeksie deur streeproes verteenwoordig. Temperatuurgrense vir infeksie lê tussen -4 en 30°C, maar daar is streng gesproke geen afsnywaardes beskikbaar nie. Om hierdie rede is besluit om 'n eksperiment uit te voer om infeksie waar te neem, waar plante onderworpe is aan toestande van hoë relatiewe humiditeit en 'n reeks van temperature, nl. 5 °C, 10°C, 15°C en 20°C. Resultate verkry deur die eksperiment het geen of verminderde infeksie aangetoon by die 20°C temperatuur vlak of by inkubasie-tydperke van minder as een uur blootstelling aan vogtige toestande. Uitsonderings op die reël het plaasgevind met skielike verminderings in temperatuur met verwydering van die plante na die glashuis. Vir beide voorkoms en siektegraad het geen infeksie voorgekom by temperature hoër of gelyk aan 22°C nie en die Pan 3349 kultivar het 'n hoër voorkoms as Karee getoon. Volgens die statistiese analises, was daar beduidende verskille vir siektegraad tussen Eksperiment 1 en 2, maar nie vir voorkoms nie. Temperature vir Eksperiment 2 was effens laer en kan verduidelik word deur die aanwesigheid van waaiers wat gekondenseerde water op die temperatuur sensors verdamp het. Dus kon die hoër waterinhoud in Eksperiment 1 hoër siektegraad tot gevolg gehad het. Toestande in die laboratorium is nie dieselfde as in die veld nie en moontlikhede vir infeksie by hoër temperature in die veld kom volgens Park (1990) algemeen voor. Hy waarsku teen ekstrapolasie van laboratorium resultate na die veld, maar hierdie studie het nogtans voortgegaan om die resultate vanaf die eksperiment as basis vir die ontwikkeling van 'n indeks vir streeproesinfeksie te gebruik. Waardes van 14 dae totale graaddae (TDDI4) is bereken vanaf totale graad-ure (TDH) van die eksperimentele waardes. TDDl4 is bereken deur die 'gradedae (DD) bymekaar te tel vanaf inokulasie tot 14 dae later en die verwantskap dan met gemiddelde voorkoms waargeneem op dag 14, te verkry. Twee liniêre regressies is verkry, een vir die 5°C - 15°C temperatuur vlak en die ander vir die 15°C - 20°C temperatuurvlak. 'n Afsnywaarde van 227 vir TDDl4 waar die twee lyne mekaar kruis, het 'n voorkoms waarde van 67 % getoon. TDDl4 is ontwikkel vanafhierdie inligting en lees soos volg: Indien TDDl4 > 227, dan is die risiko van voorkoms laag by < 67 %. Indien TDDl4 < 227, dan is die risiko van voorkoms hoog by > 67 %. TDDl4 is geëvalueer deur toetsing op 1996 - 1998 en 1999 - 2000 data. Korrekte voorspellingswaardes van hoogste en gemiddelde voorkoms waarneming was 50 % en 29 % vir 1996 - 1998 data (Tabel 4.7) en 40 % en 33 % vir 1999 - 2000 data (Tabel 4.8). TDDl4 was onprakties vir gebruik en dus is TDD7 ontwikkel deur gebruik te maak van TDD7 vir 7 dae vanaf 'n nat periode. TDD7 = 128 was 1.77 maal minder as die waarde vir TDDl4 = 227, d.w.s. 'n waarde van 128. Hierdie waarde is toe gebruik as die afsnywaarde en TDD7lees dan soos volg: Indien TDD7 > 128, dan is die risiko van voorkoms laag by < 67 %. Indien TDD7 < 128, dan is die risiko van voorkoms hoog by > 67 %. TDD7 is bevestig deur gebruik te maak van die 1999 - 2000 data en die aantal totale korrekte voorspellings is 53 % en 40 % (Table 4.10). Daar is dus besluit dat TDD7 deur die produsent gebruik kan word as 'n vroeë waarskuwingsindeks, alhoewel die indeks in die praktyk getoets sal moet word sodat die nodige verbeterings aangebring kan word. Daar word voorgestel dat navorsing op streeproes-omgewingsinteraksie voortgesit word, ook op ander siektes en dat die aanbevelings gemaak in Hoofstuk 2 ondersoek word. Ander voorstelle sluit in die beplanning van 'n ingewikkelde laboratorium eskperiment met 'n meganistiese benadering om konstante temperatuur data model in die praktyk te gebruik. Temperatuur en relatiewe humiditeit sal natuurlik varieer en die resultate sal voordelig wees vir beide produsent en navorser. A model toepasbaar op ander siektes kan waardevol wees indien die kostes van gifstowwe in ag geneem word. The suksesvolle toepassing van so 'n model sal van groot waarde wees. Per slot van rekening, kos word benodig om aan die lewe te bly en dus is volhoubare produksie van hoë kwaliteit kossoorte noodsaaklik vir die voortbestaan van die mens.
Dissertation (M.Sc.Agric. (Agrometeorology))--University of the Free State, 2001
Keywords: Wheat rusts -- Environmental aspects -- South Africa; Wheat -- Climatic factors; Weather forecasting